Munc18‐2 is required for Syntaxin 11 Localization on the Plasma Membrane in Cytotoxic T‐Lymphocytes. (2nd November 2015) - Dieckmann, Nele M.G.; Hackmann, Yvonne; Aricò, Maurizio; Griffiths, Gillian M.
Abstract : Cytotoxic T‐lymphocytes (CTL) kill their targets by cytolytic granule secretion at the immunological synapse. The Sec/Munc protein, Munc18‐2, and its binding partner Syntaxin 11 (STX11) are both required for granule secretion, with mutations in either leading to the primary immunodeficiency, Familial Haemophagocytic Lymphohistiocytosis (FHL4 and 5). Understanding how Munc18‐2 and STX11 function in CTL has been hampered by not knowing the endogenous localization of these proteins. Using a novel FHL5 Munc18‐2 mutation that results in loss of protein, cytotoxicity and degranulation together with CTL from an FHL4 patient lacking STX11, enabled us to localize endogenous STX11 and Munc18‐2 in CTL. Munc18‐2 localized predominantly to cytolytic granules with low levels associated with the plasma membrane where STX11 localized. Importantly, while Munc18‐2 localization is unaffected by the absence of STX11 in FHL4 CTL, STX11 is lost from the plasma membrane in FHL5 CTL lacking Munc18‐2. These findings support a role for Munc18‐2 in chaperoning STX11 to the plasma membrane where the final fusion events involved in secretion occur. Abstract : Understanding how Munc18‐2 and Syntaxin 11 (STX11) function in cytotoxic T‐lymphocytes (CTL) has been hampered by not knowing the endogenous localization of these proteins. Using antibodies, validated using patient CTL lacking STX11 (FHL4) and Munc18‐2 (FHL5), we show that Munc18‐2 localizes predominantly to the cytolytic granules and at lower levels on the plasma membrane, where STX11 localizes. While Munc18‐2 is unaffected in FHL4, in FHL5 STX11 is lost from the plasma membrane, where secretion occurs.